Research on Unplanned Purchases in the Serbian Market - Đukić, Suzana; Stanković, Jelena (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
Purchases of products and services are largely planned consumers´ actions, induced by defined needs and motives. However, unplanned purchases which cosumers not planned before entering a retail outlet are not rare. In a modern business environment, innovations such as the Internet, online sales, flexible working hours, "instant" loans, ATMs make it easier for consumers to make un planned purchases. Up to date research has shown that impulsive shopping, considered as an unplanned purchase, occurs in 90% of people. It is estimated that in the US, as a part of sales, impulsive purchases annually account for about 1/3 of all purchases made. The situation is similar in Europe, but with some differences and country specificities. Unplanned purchases are not the sole consequence of the impulsive way consumers respond. In addition to pure impulsivity, there will be other types of unplanned purchases, such as: a suggestion effect, a planned impulsivity, a reminder effect, and the planned purchase of a particular type, but not the brand of the product. There are many situations that affect unplanned purchases, such as the physical environment, social environment, weather, a specific situation, sudden situation, which will be further analyzed in the paper. The mass media, as well as numerous Internet communication tools, have a significant influence on the growth of unplanned purchases, which raise consumer awareness of the existence of products for they did not intend to buy. The aim of this paper is to point out the importance and basic characteristics of unplanned purchases, as well as the factors that influence consumers´ behavior to perform them. Also, based on empirical research, the most important motives for unplanned purchases will be shown, what is the frequency of the unplanned purchases and which products are purchased in an unplanned way. Most research shows that women, more than men, buy in an unplanned way. Therefore, our tendency to identify differences between consumer demographic groups in making unplanned purchases. The research will be carried in the territory of Serbia, by the survey method, using a questionnaire. The paper will analyze different buying situations as well as their relationship with unplanned purchases. The results of this analysis will contribute to the literature and implications for developing marketing strategies for unplanned purchases.